Improvements in ecosystem services from investments in natural capital - Ouyang, Zhiyun; Zheng, Hua; Xiao, Yi; Polasky, Stephen; Liu, Jianguo; Xu, Weihua; Wang, Qiao; Zhang, Lu; Xiao, Yang; Rao, Enming; Jiang, Ling; Lu, Fei; et al. (Science (American Association for the Advancement of Science), 2016)
In response to ecosystem degradation from rapid economic development, China began investing heavily in protecting and restoring natural capital starting in 2000. We report on China's first national ecosystem assessment (2000–2010), designed to quantify and help manage change in ecosystem services, including food production, carbon sequestration, soil retention, sandstorm prevention, water retention, flood mitigation, and provision of habitat for biodiversity. Overall, ecosystem services improved from 2000 to 2010, apart from habitat provision. China's national conservation policies contributed significantly to the increases in those ecosystem services.